2020
DOI: 10.1007/s12630-020-01583-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct versus indirect laryngoscopy using a Macintosh video laryngoscope: a mannequin study comparing applied forces

Abstract: Purpose Upper airway injury and sympathetic activation may be related to the forces applied during laryngoscopy. We compared the applied forces during laryngoscopy using direct and indirect visualization of a standardized mannequin glottis. Methods Force transducers were applied to the concave surface of a GlideScope T-MAC Macintosh-style video laryngoscope that can also be used as a conventional direct-view laryngoscope. Thirty-four anesthesiologists performed four laryngoscopies (two direct and two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…Most of the VL studies compared glottis visualization, intubation success rate at overall and/or the first attempt, time to intubation, and complication, with those observed using the Macintosh laryngoscope. In many studies, VL has been reported to improve glottis visualization, increase intubation success rate, reduce intubation attempts, reduce pressure on laryngeal structures, and reduce complications compared to those observed on using the Macintosh laryngoscope [3][4][5][6][7][8][9]16]. Since the VL is evolving rapidly and has various advantages over Macintosh laryngoscope, it is considered that VL will become a routine practice in airway management during anesthesia in place of the Macintosh laryngoscope in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the VL studies compared glottis visualization, intubation success rate at overall and/or the first attempt, time to intubation, and complication, with those observed using the Macintosh laryngoscope. In many studies, VL has been reported to improve glottis visualization, increase intubation success rate, reduce intubation attempts, reduce pressure on laryngeal structures, and reduce complications compared to those observed on using the Macintosh laryngoscope [3][4][5][6][7][8][9]16]. Since the VL is evolving rapidly and has various advantages over Macintosh laryngoscope, it is considered that VL will become a routine practice in airway management during anesthesia in place of the Macintosh laryngoscope in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the search for intubation methods alternative to direct laryngoscopy is one of the main areas of research in emergency medicine. According to numerous studies, videolaryngoscopy, compared to direct laryngoscopy, shows a faster learning curve [20,21], as well as offering better glottis visibility and higher intubation efficiency, especially for intubation in difficult conditions (i.e., difficult airway conditions or difficult access to patients airway) [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…There is some literature discussing the utility and effectiveness of VL in the context of emergency medicine and in intensive care settings by non-expert providers. 2,5,6,8 Studies have been conducted retroactively on large patient populations and on manikins to better understand the utility of DL in the prehospital emergency setting. For example, one manikin study established that the median force applied to the concave surface of the laryngoscope during intubation attempts using VL was lower than the force applied during DL to achieve >80% of glottic opening aperture, indicating one advantage of using VL by Emergency Medical Services personnel.…”
Section: Introductionmentioning
confidence: 99%